2001
DOI: 10.1080/00288330.2001.9517006
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of post‐settlement abaloneHaliotis iriscaused by conspecific adults and wave exposure

Abstract: Experimental studies of post-settlement abalone (Haliotis iris Martyn) indicate that wave exposure and conspecific adults may be important sources of mortality. In aquarium studies, exposure of post-settlement abalone to grazing by sea urchins (Evechinus chloroticus) and starfish (Patiriella regularis), animals common in the subtidal habitat of H. iris, resulted in similar survival to control treatments (no grazers). However, in the presence of conspecific adults, the survival of post-settlement juveniles was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Free space on the substratum is necessary for abalone settlement, and crustose coralline algae (and their associated chemicals and biofilms) are known to induce settlement of abalone larvae (Morse et al 1979, Douros 1985, Day & Branch 2002a. The presence of conspecific individuals, particularly adults, may also be important for settlement as their grazing activities might maintain the cover of crustose coralline algae (Douros 1985) and their mucus on the substratum may act as a positive settlement cue for abalone larvae (Bryan & Qian 1998), but Naylor & McShane (2001) have reported that adult abalone can smother conspecific recruits. The increased cover of tube worms and tube snails documented in this study may be particularly detrimental to recolonization because tube worms have been shown to prey on abalone larvae (Naylor & McShane 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Free space on the substratum is necessary for abalone settlement, and crustose coralline algae (and their associated chemicals and biofilms) are known to induce settlement of abalone larvae (Morse et al 1979, Douros 1985, Day & Branch 2002a. The presence of conspecific individuals, particularly adults, may also be important for settlement as their grazing activities might maintain the cover of crustose coralline algae (Douros 1985) and their mucus on the substratum may act as a positive settlement cue for abalone larvae (Bryan & Qian 1998), but Naylor & McShane (2001) have reported that adult abalone can smother conspecific recruits. The increased cover of tube worms and tube snails documented in this study may be particularly detrimental to recolonization because tube worms have been shown to prey on abalone larvae (Naylor & McShane 1997).…”
Section: Discussionmentioning
confidence: 99%
“…2 d, Ray & Stoner 1995) and abalone species (ca. 25−36% within 3 d, Naylor & McShane 2001). Estimates of total post-settlement mortality in the present study were also substantial (ca.…”
Section: Discussionmentioning
confidence: 52%
“…Substantial mortality during early post-settlement life has long been suggested and demonstrated across several marine taxa (Connell 1961, Thorson 1966, Gosselin & Qian 1997, Hunt & Scheibling 1997, including reef fish (Searcy & Sponaugle 2001, Doherty et al 2004, mobile invertebrates such as crabs, abalone and other gastropod species (Ray & Stoner 1995, Moksnes et al 1998, Naylor & McShane 2001) and a variety of sessile invertebrates (Hurlbut 1991, Gosselin & Qian 1996, Marshall & Keough 2003. Certainly, juvenile mortality in benthic marine invertebrates is greater than 90% in the majority of studies (Gosselin & Qian 1997), identifying this period as especially important in the life history progression of benthic organisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations